Quantitative Whole Body Scintigraphy – A Simplified Approach - Marienhagen, J.; Männer, P.; Bock, E.; Schönberger, J.; Ellies, Chr. (Nuklearmedizin - NuclearMedicine, 1996)
In this paper we present investigations on a simplified method of quantitative whole body scintigraphy by using a dual head LFOV-gamma camera and a calibration algorithm without the need of additional attenuation or scatter correction. Validation of this approach to the anthropomorphic phantom as well as in patient studies showed a high accuracy concerning quantification of whole body activity (102.8% and 97.72%, resp.), by contrast organ activities were recovered with an error range up to 12%. The described method can be easily performed using commercially available software packages and is recommendable especially for quantitative whole body scintigraphy in a clinical setting.In dieser Studie wird eine vereinfachte Methode zur quantitativen Szintigraphie mittels einer LFOV- Doppelkopf-Ganzkörperkamera vorgestellt. Das Verfahren verwendet einen patientenindividuellen Kalibrierungsfaktor und verzichtet auf zusätzliche externe Schwächungs- bzw. Scatter-korrekturen. Experimentelle Quantifizierungsuntersuchungen zeigten sowohl am Modell des anthropomorphen Phantoms wie auch in Anwendung am Patienten eine hohe Wiederfindungsrate der Ganzkörperaktivität (im Mittel 102,8% bzw. 97,72%). Bei der Berechnung von Organaktivitäten wurde ein Quantifizierungsfehler von bis zu 12% beobachtet. Die beschriebene Methode kann ohne großen Aufwand mit kommerziell erhältlicher Standardsoftware implementiert werden und eignet sich besonders für die quantitative Ganzkörperszintigraphie bei klinischen Fragestellungen.
Keywords: Quantitative whole body scintigraphy; conjugate counting; internal calibration; anthropomorphic phantom